Library staff member in the Film & Video Department. - Unknown (Forsyth County Public Library, 1980)
Photo made in the 1980s.
Library staff member Nancy Golden in the Film & Video Department, operating the film inspection equipment.
Keywords: Forsyth County (N.C.) -- History -- Sources; Forsyth County (N.C.) -- History -- Pictorial works; Digital Forsyth; Winston-Salem (N.C.); Forsyth County Public Library